E-Goverment Pada Pekon Berbasis Web Mobile (Studi Kasus Way Sindi Hanuan) - susilowati, Tri; Taufik; Andriyani, Novita (Jurnal Informatika, 2025)
Way Sindi Hanuan for visitors and is the basis for further tourism development. In this very modern era, people are required to know developments in existing technology. Currently, Pekon Way Sindi Hanuan still uses a manual system in providing information, which ultimately means that the public cannot get the information they need at any time, so there is a lot of unknown information. The aim of this research is to build e-government in the Way Sindi Hanuan pekon based on Web Mobile to improve services to the Pekon community, and introduce the Way Sindi Hanuan pekon tourist attraction, so that many tourists visit the Way Sindi pekon. E-gov was built using SDLC, DFD and ERD methods in the mobile web design process. This system will have several features, namely the Pekon profile, population data and related information on Pekon. The results of this research are able to assist Pekon officials in conveying information to the public and become a means of providing information on Pekon Way Sindi Hanuan tourism for visitors and become the basis for further tourism development